Validation of a community-based application of the Portuguese version of the survey on Social and Emotional Skills – Child/Youth Form - Castro, Catarina; Barata, Clara; Alexandre, Joana; Colaço, Carla (Frontiers in Psychology, 2023)
Children and adolescents’ social and emotional skills have been gaining attention in diverse settings. With over 100 conceptual frameworks available, there is now a common move towards framing these skills as social and emotional learning (SEL), assuming that they are not only amiable to development, but also malleable to change as a product of intervention. As such, there is a strong need for a comprehensive measure to effectively evaluate such skills, validated for different age groups in children and young people, and applicable to both educational contexts and community settings. This paper presents the validation of the Portuguese adaptation of the Child/Youth form of the Survey on Social and Emotional Skills (SSES), in the scope of the Gulbenkian Academies for Knowledge initiative with a sample of 7831 participants between 8 and 17 years old (M=11.79, SD=2.94). Results show that the measure has good internal consistency and sensitivity, while also being sensitive to change over time. Preliminary factor analysis shows promise, although further research is necessary. Discussion reflects on the value of the Child/Youth form of the SSES as a comprehensive measure to be used by community and educational professionals to monitor skill development and improve their work on SEL.